ASPEK SANKSI PIDANA DALAM KORUPSI KORPORSI PANDANGAN FUQAHA DAN UNDANG-UNDANG DI INDONESIA - Dedi Ratno (INTEGRATIF |Jurnal Magister Pendidikan Agama Islam, 2023)
This research was conducted to find out how the Imams of Madzhab thought about corruption and what the basics of each thought were. The research method used in this study is normative juridical research and it can be concluded: 1. Corruption in the minds of the Imams of Madzhab is an act of violating the Shari'a. Islamic Shari'a aims to realize the benefit for humanity with what is known as maqashidussy syaria'ah. From the perspective of the wider context of Islamic teachings, corruption is an act that is contrary to the principles of justice, accountability and responsibility. Corruption can cause various distortions to the life of the State and society which can be categorized into acts of damage to the face of the earth (facade). 2. The rationale of the Imam madzhab for punishment for perpetrators of corruption is to place corruption in the category of takzir takzir, takzir is a legal sanction that is imposed on a person who commits a crime that commits violations related to the rights of Allah SWT and human rights, and violations - the violation is not explicitly determined in the form of sanctions in the texts of the Al-Quran and hadith, because it is not strictly determined, the takzir becomes the competence of the judge or local authorities. Takzir legal sanctions can be in the form of prison sentences, fines, inclusion in the list of disgraceful persons, dismissal laws, and even the death penalty.